2018
DOI: 10.1080/07481187.2017.1416431
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the latent factor structure and construct validity of the stigma of suicide scale-short form

Abstract: A major limitation of research on attitudes toward suicide is that most measures lack evidence of a stable factor structure. To investigate the structure of recently developed stigma of suicide scale-short form (SOSS-SF), we conducted an exploratory factor analysis in a sample of 499 undergraduates. Results revealed a three-factor structure: Stigma, Isolation/Depression, and Glorification/Normalization. We also identified good convergent and discriminant validity between the SOSS-SF and related constructs. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
3
14
1
3
Order By: Relevance
“…The impact of these three suicide prevention videos on measures of young adults' stigma of helpseeking were examined, starting with a range of evidence-based scales used in prior suicide prevention research [14]. The Self-Stigma of Seeking Help scale (SSOSH) by Vogel, Wade, and Haake [29] was used as the basis for our aggregate analysis based on our pilot results coupled with literature showing that reductions in estimated mean perceived self-stigma are tied to increases in help-seeking behavior [24,[35][36][37][38][39][40]. In Vogel's groundbreaking paper based on a sample of 655 college students, they found that there was a difference of 3.0 (p = 0.032 from an unequal variances t-test) in the estimated mean SSOSH scores between a group of students who sought psychological services over a two-month period and those who did not.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of these three suicide prevention videos on measures of young adults' stigma of helpseeking were examined, starting with a range of evidence-based scales used in prior suicide prevention research [14]. The Self-Stigma of Seeking Help scale (SSOSH) by Vogel, Wade, and Haake [29] was used as the basis for our aggregate analysis based on our pilot results coupled with literature showing that reductions in estimated mean perceived self-stigma are tied to increases in help-seeking behavior [24,[35][36][37][38][39][40]. In Vogel's groundbreaking paper based on a sample of 655 college students, they found that there was a difference of 3.0 (p = 0.032 from an unequal variances t-test) in the estimated mean SSOSH scores between a group of students who sought psychological services over a two-month period and those who did not.…”
Section: Methodsmentioning
confidence: 99%
“…Means for the Stigma, Isolation/Depression and Normalisation/Glorification subscales in this sample were 1.84 (SD ¼ 0.98), 4.10 (SD ¼ 0.85) and 2.56 (SD ¼ 0.97), respectively. The scale has previously been shown to have strong psychometric properties in similar samples (Batterham et al, 2013b;Williams, Cero, Gauthier, & Witte, 2018). The focus of the current study was only on the stigma subscale, which comprised eight items with high internal consistency (Cronbach A ¼ 0.88).…”
Section: Methodsmentioning
confidence: 99%
“…Diese Werte hängen vermutlich mit der geringen Itemanzahl (4) in den beiden Subskalen zusammen. Andere internationale Studien konnten für die interne Konsistenz der SOSS-SF höhere Werte ermitteln [14,26,27], allerdings nutzten diese für die Validierung jeweils ausschließlich akademische Stichproben. Die geringere interne Konsistenz in dieser Erhebung steht möglicherweise in Zusammenhang mit einer heterogeneren Stichprobe.…”
Section: Subskalenunclassified
“…Die Items "entschlossen" und "verloren" zeigten vergleichsweise geringe Faktorladungen auf dem jeweiligen Faktor (jeweils < 0,5). Da aber aufgrund der großen Stichprobe (N = 2002) zufällige Ladungsmuster ausgeschlossen werden können [26] und, um die deutsche und australische Version der SOSS-SF-D international vergleichen zu können, wurde darauf verzichtet, diese Items aus den Analysen auszuschließen.…”
Section: Subskalenunclassified
See 1 more Smart Citation